Identifikasi Risiko dan Perancangan Mitigasi Risiko Mutu Di PT Ryan Eka Pratama Balikpapan - Richard Ryan Bernardo; I Nyoman Sutapa (Jurnal Titra, 2020)
The aim of this research is to identify risk and mitigation at PT Ryan Eka Pratama. PT Ryan Eka Pratama does not yet have the ISO 9001:2015 certification. One of the ISO 9001:2015 requirements are risk identifigaton and mitigation. The research had done directly on field to identify the risk from quality side. Based on the findings, developed risk mitigation strategies that are needed